(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
Abstract The success of an agency can be determined by the achievement of the planned goals. Efforts can be made to achieve this goal by utilizing the resources owned by both human resources and other resources, such as capital and office infrastructure. Humans are a crucial resource for an institution because humans have the ability to work together, set goals and work to achieve goals. The purpose of this study was to determine the effectiveness of the development of service facilities and infrastructure at the Karunrung Village Office, Rappocini District, Makassar City. This research uses quantitative research type with descriptive research type with the number of respondents as many as 32 people. The results of this study indicate that the effectiveness of the development of facilities and infrastructure is categorized as good. It can be seen from the recapitulation of each indicator including: Efficiency Indicator with a percentage of 80.83%, Flexibility Indicator with a percentage of 85.93%, Satisfaction Indicator with a percentage of 69.6%, Excellence Indicator with a percentage of 70.9%, Development Indicator with a percentage of 70.6%. Keywords: effectiveness, development, facilities and infrastructure